2017
DOI: 10.1016/j.marpolbul.2017.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing and culture-based techniques offer complementary insights into fungi and prokaryotes in beach sands

Abstract: • Beach sands represent reservoirs for a variety of bacterial, fungal, and protozoan pathogens. 1 • Epidemiological studies and monitoring efforts have only recently been explored to protect public health. 1 • Current monitoring efforts are based on culture-based enumeration of fecal indicator bacteria and selected fungal pathogens. 2 • Next-generation sequencing (NGS) methods are increasingly being used to more completely characterize microbial communities in sands. 3 • Taken together, NGS and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…They are different in that the Chao1 estimator gives greater weight to low abundance species (species with less than 10 individuals in a sample), while the ACE estimator gives greater weight to species sample coverage (species with more than 10 individuals in a sample) (Kim et al 2017). In this study, however, both estimators still showed high bacterial species richness in all beach sand samples, as also observed in other beach sand samples (Mudryk et al 2013;Romão et al 2017). This confirms earlier findings that beach sands are microhabitats teaming with microbial life (Sabino et al 2014;Whitman et al 2014;Solo-Gabriele et al 2015).…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…They are different in that the Chao1 estimator gives greater weight to low abundance species (species with less than 10 individuals in a sample), while the ACE estimator gives greater weight to species sample coverage (species with more than 10 individuals in a sample) (Kim et al 2017). In this study, however, both estimators still showed high bacterial species richness in all beach sand samples, as also observed in other beach sand samples (Mudryk et al 2013;Romão et al 2017). This confirms earlier findings that beach sands are microhabitats teaming with microbial life (Sabino et al 2014;Whitman et al 2014;Solo-Gabriele et al 2015).…”
Section: Discussioncontrasting
confidence: 42%
“…Therefore, understanding the microbial community structure and biodiversity of beach sand is useful for assessing the ecological health of the beach sand, as higher biodiversity usually confers better resistance and resilience against environmental perturbation and contamination (Cui et al 2013). The dominance of bacteria belonging to the phyla Proteobacteria, Bacteroidetes, Planctomycetes, Actinobacteria, and Gemmatimonadetes in beach sands has earlier been documented in coastal beach samples (Zheng et al 2014;Romão et al 2017). This may indicate that these phyla have evolved to be the main indigenous bacterial communities in coastal intertidal zones.…”
Section: Discussionmentioning
confidence: 99%
“…In intertidal sands, a few studies have characterized the diversity of microbes associated with several potential metabolic functions, as well as potential human pathogens (Yamahara et al, 2007;Cui et al, 2013;Staley and Sadowsky, 2016;Romão et al, 2017). In these studies, the intertidal sands FIGURE 2 | Geographic locations of globally sampled beach aquifers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the indigenous microbial sand communities are also one of the most critical factors for preventing the colonization of harmful exogenous microorganisms, such as fecal indicator bacteria and pathogens, on beach sands [5,6]. Thus, increasing attention is being paid to the biogeographic distribution pattern of sand microbial communities and its driving forces [2,4,[7][8][9]. The importance of environmental filtering in shaping the assembly of sand microbial communities has highlighted, and a significant body of literature has demonstrated, that the distance from shoreline, sand grain size, moisture, temperature, nutrients (including organic and inorganic matters), and chemical contaminants are major environmental factors shaping sand microbial communities [2,7,8,10,11].…”
Section: Introductionmentioning
confidence: 99%